2020
DOI: 10.3390/antiox9101002
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Genus Cotoneaster (Rosaceae): Phytochemistry, Biological Activity, and Toxicology

Abstract: Traditional herbal medicines have become a subject of global importance with both medical and economic implications. The regular consumption of herbal drugs has led to serious concerns regarding their quality, effectiveness, and safety. Thus, relevant scientific evidence has become an important criterion for the acceptance of traditional health claims. The genus Cotoneaster Medikus provides numerous species traditionally used in Asian medicine for the treatment of haemorrhoids, diabetes, and cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…Many researchers have reported the biomedical applications of herbal medicines [ 346 , 347 , 348 , 349 , 350 , 351 , 352 , 353 , 354 , 355 , 356 , 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 , 365 ]. Antibiotics and other chemical antimicrobial agents including metal oxide and metal nanoparticles can inhibit bacteria growth but also lead to ROS generation and other side effects.…”
Section: Conclusion and The Future Outlookmentioning
confidence: 99%
“…Many researchers have reported the biomedical applications of herbal medicines [ 346 , 347 , 348 , 349 , 350 , 351 , 352 , 353 , 354 , 355 , 356 , 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 , 365 ]. Antibiotics and other chemical antimicrobial agents including metal oxide and metal nanoparticles can inhibit bacteria growth but also lead to ROS generation and other side effects.…”
Section: Conclusion and The Future Outlookmentioning
confidence: 99%
“…Since ancient times, medicinal and aromatic plants have been recognized as reliable sources of health-promoting bioactive agents and a valuable source for finding new drug leads ( Kicel, 2020 ; Annaz et al, 2022 ). Recently, several serious concerns have been raised about the quality, efficacy, and safety of synthetic drugs ( Sahoo et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless in the mentioned study (15), no difference observed at 48 hours. Cotoneaster manna has laxative effect, owing to its important ingredient mannitol, and it is supposed that, this is by this mechanism that excretion of bilirubin is facilitated (16). However, the exact mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%